THE IMPACT OF THE COVID-19 CRISIS ON THE ECONOMIC BURDEN OF DEPRESSIVE DISORDERS AMONG THE WORKING-AGE POPULATION, CONSIDERING DIFFERENT FUNCTIONAL AREAS IN POLAND - Agnieszka Jakubowska (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The growing prevalence of chronic depressive disorders among the working-age population represents a serious and increasingly costly challenge for the economy. This study aims to assess the economic burden of depressive disorders in this group, taking into account spatial variation across functional areas (urban and rural districts) in Poland. It also examines the impact of the COVID-19 pandemic on inequality levels between differently urbanised areas. The analysis is based on data from EUROSTAT, the Polish Central Statistical Office (CSO), and the Ministry of Health for the period 2016-2022. The working hypothesis assumes that the pandemic triggered a long-term increase in the average burden of depressive disorders, accompanied by a decline in regional disparities due to a convergence process. The burden is measured as absenteeism from work due to illness, expressed per thousand working-age individuals in each district. Convergence analysis is applied to evaluate the evolution of disparities. The results reveal pronounced inequalities, with the highest burden in highly urbanised areas. However, between 2016 and 2022, a gradual reduction in these disparities was observed, despite a general increase in the overall burden – indicating negative convergence. These findings add to the literature by highlighting the spatial dimension of mental health inequalities and the broader economic implications of the pandemic.